The influence of giving rewards in increasing students' motivation and learning outcomes at SDN 256 Benteng Jati - Saputra, Arif; Manda, Ibrahim; Hermansyah, Sam; Ahmad, Jamaluddin; Sadapotto, Andi; Efendy Rasyid, Rustam (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to analyze: (1) the effect of applying the reward method in the form of achievement stars on the English learning motivation of fifth-grade students at SDN 256 Benteng Jati; (2) the effect of applying the reward method in the form of achievement stars on their English learning outcomes; and (3) the overall influence of the reward method on students’ motivation and learning outcomes. The research employed a quasi-experimental design using the Pretest-Posttest Non-Equivalent Control Group Design. The population consisted of 110 students of SDN 256 Benteng Jati, while the sample was the fifth-grade students divided into two classes: Class Va (11 students) as the experimental group and Class Vb (11 students) as the control group. Data were analyzed using both descriptive and inferential statistical techniques. The findings reveal that the implementation of the reward method significantly affected the students’ motivation in learning English and also improved their learning outcomes. Thus, providing rewards in the form of achievement stars proved to be an effective strategy to enhance both learning motivation and achievement among fifth-grade students.